María Cristina Quintero, Gendering the Crown in the Spanish Baroque «Comedia» - Elizabeth Wright (Universitat Autònoma de Barcelona, 2015)
Reseña de María Cristina Quintero, Gendering the Crown in the Spanish Baroque «Comedia», Ashgate, Surrey, 2012, 248 pp. ISBN: 9781409439639.